1998
DOI: 10.1038/bjc.1998.687
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β1 (TGF-β1) is a preoperative prognostic indicator in advanced gastric carcinoma

Abstract: Summary It has been generally accepted that transforming growth factor 31 (TGF-j1l) has both negative and positive effects on tumour growth and progression. This study analysed the prognostic value of TGF-1l mRNA in advanced gastric carcinoma. A reverse transcriptase-polymerase chain reaction analysis (RT-PCR) was used for TGF-J1 in endoscopic biopsy specimens from 42 advanced gastric carcinomas. Thirty specimens expressed TGF-p1 mRNA while 12 specimens did not. The follow-up duration ranged from 4 to 37 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…Enhanced expression of TGF-β1 has also been reported in gastric cancers and in the fibrosis associated with scirrhous gastric carcinoma (Mahara et al, 1994;Naef et al, 1997). Furthermore, the expression of TGF-β1 in advanced gastric cancers is also associated with a shorter survival of these patients (Nakamura et al, 1998). The mechanism of TGF-β1 function in these cancers is believed to be mediated primarily by the stimulation of the extracellular matrix and suppression of an adequate immunological response.…”
Section: Discussionmentioning
confidence: 98%
“…Enhanced expression of TGF-β1 has also been reported in gastric cancers and in the fibrosis associated with scirrhous gastric carcinoma (Mahara et al, 1994;Naef et al, 1997). Furthermore, the expression of TGF-β1 in advanced gastric cancers is also associated with a shorter survival of these patients (Nakamura et al, 1998). The mechanism of TGF-β1 function in these cancers is believed to be mediated primarily by the stimulation of the extracellular matrix and suppression of an adequate immunological response.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have shown the involvement of TGF-b1 in different types of cancer, including gastric, colorectal and breast cancer (Naef et al, 1997;Nakamura et al, 1998;Maehara et al, 1999;Saito et al, 1999;Desruisseau et al, 2006). Most of these studies assessed tissue TGF-b1 levels by mRNA expression, immunohistochemistry or serum TGF-b1 levels, which give either less information on the actual protein levels, are difficult to quantify or do not reflect local effects.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies showed TGF-b expression in tumour cells (Naef et al, 1997;Park et al, 1997;Maehara et al, 1999;Saito et al, 1999) and sporadic in fibroblasts (Naef et al, 1997). Positive TGF-b1 immunostaining was found to be related to invasion and metastasis of gastric cancer (Nakamura et al, 1998;Maehara et al, 1999). Finally, gastric cancer patients showed strongly increased tissue TGF-b1 levels and, unexpectedly, reduced serum TGF-b1 levels .…”
mentioning
confidence: 93%
“…Although studies have shown that TGFβ1 expression is closely linked to the prognosis of gastric cancer (26,27), neither the polymorphisms of TGFB1 -509C/T and TGFBR2 -875A/G nor the combination of the two SNPs revealed a correlation with patient survival in this study, consistent with the study in the uS population (11). A possible explanation is that overall survival is determined, not only by factors involved in gastric cancer disease activity, but also by underlying diseases and other complications.…”
Section: Discussionmentioning
confidence: 99%